2006
DOI: 10.1128/iai.00135-06
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Region of Bacteroides fragilis Toxin Is Essential to Its Biological Activity

Abstract: To evaluate the role of the C-terminal region in Bacteroides fragilis toxin (BFT) activity, processing, and secretion, sequential C-terminal truncation and point mutations were created by site-directed mutagenesis. Determination of BFT activity on HT29/C1 cells, cleavage of E-cadherin, and the capacity to induce interleukin-8 secretion by wild-type BFT and C-terminal deletion mutants showed that deletion of only 2 amino acid residues at the C terminus significantly reduced BFT biological activity and deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…In turn, there is only a low, 25%, identity of the peptide sequence of MPII with that of FRAs (21,26,30). Whereas FRAs have been the focus of multiple studies by others (13,14,19,21,30,32,(63)(64)(65)(66)(67)(68)(69), the characteristics of MPII are completely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, there is only a low, 25%, identity of the peptide sequence of MPII with that of FRAs (21,26,30). Whereas FRAs have been the focus of multiple studies by others (13,14,19,21,30,32,(63)(64)(65)(66)(67)(68)(69), the characteristics of MPII are completely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Further dissection of the initial steps in BFT interaction with the cell and the role(s) of the BFT protease domain and/or cellular proteases in the mechanism of action of BFT has been limited because we have not identified a protease inhibitor that specifically inhibits eukaryotic proteases, but not BFT. Similarly, mutational analyses of BFT suggest it is a highly conserved protein without, as yet, a defined binding domain distinct from its protease domain (Franco et al, 2005;Sears et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although BFT has been reported to be autoproteolytic (61,116), BFT metalloprotease point mutations do not alter the intracellular processing and secretion of BFT by B. fragilis, suggesting that other intracellular B. fragilis proteases process the holotoxin to mature BFT (28). Additional mutational analysis of the C-terminal region of BFT indicated that this region is intolerant to modest amino acid deletions, suggesting that this region is also important for BFT activity (104). Truncation mutations removing only two C-terminal amino acids reduced BFT biologic activity, and removal of eight (or more) amino acids obliterated it.…”
Section: Bft Genetics and Protein Structurementioning
confidence: 99%
“…Truncation mutations removing only two C-terminal amino acids reduced BFT biologic activity, and removal of eight (or more) amino acids obliterated it. BFT mutants lacking eight or more C-terminal amino acids were expressed similar to wild-type toxin, but the mutant BFTs were unstable (104).…”
Section: Bft Genetics and Protein Structurementioning
confidence: 99%